BODY COMPOSITION AND SOMATOTYPIC PROFILE OF ROWERS FROM MARINE CORPS AND MEMBERS TO BRAZILIAN ROWING CONFEDERATION (Fiep Bulletin - online, 2013)
Competitive rowing is a sporting modality which demands high energetic expenditure, in which the intensity and duration of physical exercise varies in accord with the training phase. This study aimed to describe body composition and somatotypic features of rowing athletes from marine corps and members to Brazilian Rowing Confederation. A cross-sectional, descriptive, and quantitative study was performed with 11 male athletes, all volunteers, with age between 20 and 24 years, belonging to marine corps and members to Brazilian Rowing Confederation. The following parameters were analyzed: total body mass (Kg), height (m), nine skinfolds, two muscle girths and three bone breadths. Data analysis was initially performed to describe the studied groups by absolute and relative frequencies, and measures of central tendency and dispersion, using the statistical software SPSS version 10.0. We used the method proposed by somatotype Heath and Carter. Data are shown as mean±SD. The age of the athletes evaluated was 21.72±1.27 years, and the mean body mass and height were 81.74±7.50Kg and 186.91±4.30cm, respectively. The mean body fat percentage was 10.21±3.87. Somatotypic components of the athletes evaluated were: mesomorphy 3.65±0.58; endomorphy 2.30±0.68 and; ectomorphy 2.98±0.66. Most of the athletes have the
Keywords: Rowing; Body Composition; Somatotype